Factors Contributing to Natural Resource Degradation and Conservation Strategies from the Perspective of Residents of Baghlan Province - Yaquby, Abdul Maruf; Ahmady, Basir Ahmad; Hussainy, Sharafullah (Journal of Natural Sciences – Kabul University, 2026)
Forests and vegetation cover are among the most critical natural resources and play a fundamental role in environmental sustainability and the survival of living organisms. Baghlan Province, despite having a relatively extensive vegetation cover, has experienced a significant decline in these resources over the past few decades. This study was conducted in 2024 to identify factors contributing to vegetation cover degradation and to propose appropriate conservation strategies. Data were collected through questionnaires using a simple random sampling method from residents of various districts of the province. The results indicate that 32.4% and 29.6% of respondents assessed vegetation cover degradation as high and very high, respectively. Furthermore, 50.8% identified overexploitation by local communities, 33.3% conversion to agricultural land, 12.5% overgrazing by livestock, and 3.4% wildfires as the main drivers of degradation. Finally, improving household economic conditions and effectively implementing conservation laws are proposed as key strategies to reduce degradation and restore vegetation cover.